Digital Literacy for Women's Empowerment: A Solution to Grow Awareness of Countering Hoaxes - Ahmadi, Dadi; Rini Rinawati; Dedeh Fardiah; Ferry Darmawan; Mutia Umar; Nia Kurniati Syam (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
The purpose of this study is to explore the effectiveness of digital literacy programmes for women to raise awareness and combat hoaxes. The object of the research is the women's recitation community who are members of the Aisyiyah organisation. The importance of digital literacy in today's digital era and the need for continued investment in programmes to help women become more digitally literate. Using a quasi-experimental design, this study used pre-test and post-test data to measure awareness and combat hoaxes. Data was collected from primary and secondary sources, including surveys and literature reviews. The results showed an improvement in literacy and this reflected the participants' understanding and application of digital literacy skills, including social media, blogs, videos, images and editing tools. A comparison between the pre and post-test results and the change in error rates can give an idea of the increase or decrease in digital literacy skills after the programme.